Can environmental contamination be explained by particular traits associated with patients?. Issue 3 (March 2020) - Pilmis, B.; Billard-Pomares, T.; Martin, M.; Clarempuy, C.; Lemezo, C.; Saint-Marc, C.; Bourlon, N.; Seytre, D.; Carbonnelle, E.; Zahar, J-R.
SUMMARY: Background: Little is known about patient risk factors associated with environmental contamination. Aim: To evaluate the rate of environmental contamination and to investigate individual risk factors. Methods: A prospective cohort study was conducted. Each day, five rooms occupied by patients were selected. Five critical surfaces were systematically swabbed twice a day before and after cleaning. Clinical characteristics of all patients were collected. Logisitic regression was performed to evaluate the association between environmental contamination and patients' characteristics. Findings: A total of 107 consecutive patients were included and 1052 environmental samples were performed. Nineteen (18%) patients were known previously colonized/infected with a multidrug-resistant organism (MDRO). Respectively, 723 (69%) and 112 (11%) samples grew with ≥1 and >2.5 cfu/cm 2 bacteria, resulting in 62 (58%) contaminated rooms. Considering positive samples with at least one pathogenic bacterium, 16 (15%) rooms were contaminated. By univariate and multivariate analysis, no variables analysed were associated with the environmental contamination. Considering contaminated rooms with >2.5 cfu/cm 2, three factors were protective for environmental contamination: known MDRO carriers/infected patients (odds ratio: 0.25; 95% confidence interval: 0.09–0.72; P = 0.01), patients with urinary catheter (0.19; 0.04–0.89; P = 0.03) and hospitalization in single room (0.3; 0.15–0.6; P < 0.001). Conclusion: This study was conducted in a non-outbreak situation and showed a low rate of environmental contamination with pathogenic bacteria. Only 11% of environmental samples grew with >2.5 cfu/cm 2, and they were related to non-pathogenic bacteria. No risk factors associated with environmental contamination were identified.